Marriage, its forms and special features of the Bolgarians' prenuptial communication in Odessa region during the Soviet period - Ганчев, Олександр (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
In the following article marriage is discussed as a form of social relationships among the Bolgarians in Odessa region while public affairs transition from androcentric society to civil law relations.The role of economic aspect is defined in procedures of entering into marriage during XX century. The portrait of "ideal" partner is described according to traditional society's demands and also its changes are mentioned under the challenge of that time. Transformations in prenuptial communication in the second half of XX century are recorded together with the Bolgarians' attitude to the institution of marriage in general. The author makes a conclusion as for changes in the institution of marriage and its semantic issues. Although, before the Soviet regime marriage was seen as a stable economic position in androcentric culture of Bulgarian village, during the second half of XX century wedlock was being perceived as a spiritual union by the general public. Prenuptial communication was getting open for young people and it caused contraventions of main prohibited cultural traditions. Moreover, forms of marriage got changed, too. During the second half of XX century the main form to get married remained as a complex of wedding rituals widespread but transformed for that time. However, most wedding rituals kept their original forms such as church weddings, regenerated only after the Soviet Union's collapse while forming independent Ukraine, and marriage registration.